Synergistic effect of manual dynamic agitation and ethylenediaminetetraacetic acid containing 0.25% cetrimide on smear layer removal: An in vitro study - Tadkamol Krongbaramee (2020)
© 2020 Saudi Endodontic Journal | Published by Wolters Kluwer - Medknow. Introduction: This study aims to study the efficiency of manual dynamic agitation (MDA) combined with ethylenediaminetetraacetic acid (EDTA) containing 0.25% cetrimide in smear layer removal of mechanically prepared root canals after final irrigation. Materials and Methods: The root canals of 120 premolars were prepared using Mtwo® rotary instruments. The roots were randomly divided into six groups (n = 20): negative control (G1), irrigated with normal saline, and positive control (G2), irrigated with 17% EDTA followed by 2.5% sodium hypochlorite (NaOCl). The reaming four groups were irrigated with 17% EDTA followed by 2.5% NaOCl with MDA and agitated with gutta-percha (G3), irrigated with 17% EDTA followed by 2.5% NaOCl (both with MDA) (G4), irrigated with 17% EDTA containing 0.25% cetrimide followed by 2.5% NaOCl (both with MDA) (G5), and irrigated with SmearClear™ EDTA followed by 2.5% NaOCl (both with MDA) (G6). Subsequently, the specimens were evaluated under scanning electron microscopy. The amount of smear layer in each specimen, 1 mm, 3 mm, and 5 mm of the apical third of the root canal, was scored using Gutmann's scoring system. Data were statistically analyzed using the Kruskal-Wallis and Mann-Whitney U tests. Results: The least smear layer score was observed in Group 5 (P < 0.05). Utilizing MDA with EDTA and NaOCl (Groups 4-6) led to significantly reduced smear layer score compared to negative and positive control. Even MDA for NaOCl alone (Group 3) had significantly cleaner walls compared to negative and positive control (P < 0.05). Conclusions: Supplementation with MDA in the final root canal irrigation step promoted a significantly cleaner surface of the mechanically prepared root canal wall at the apical level. Further, the use of EDTA containing 0.25% cetrimide significantly improved smear layer removal.